Effect of cathode inlet manifold configuration on performance of 10-cell proton-exchange membrane fuel cell - Kim, Seo Young; Kim, Won Nyun (ELSEVIER SCIENCE BV, 2007)
A 10-cell proton-exchange membrane fuel cell (PEMFC) stack with 10 cathode flow channels is employed to investigate the effect of airflow inlet manifold configuration on the overall performance. Four different types of airflow inlet manifold with a 90 degrees turn are considered. First, the flow patterns according to the manifold configuration are numerically sought. The computational result for the improved inlet manifold predicts about 8.5% increase in the uniformity of the airflow distribution. The experiments are carried out to confirm the numerical predictions by measuring actual airflow distributions through the fuel cell stack. The polarization curve and the power curve for the 10-cell PEMFC are also obtained to determine the effect of inlet manifold configuration on the actual performance. The maximum power output increases by up to 10.3% on using the improved airflow inlet manifold. (c) 2007 Elsevier B.V. All rights reserved.